2023
DOI: 10.1038/s41541-023-00721-y
|View full text |Cite
|
Sign up to set email alerts
|

Screening of immunogenic proteins and evaluation of vaccine candidates against Mycoplasma synoviae

Abstract: Mycoplasma synoviae (M. synoviae) is a serious avian pathogen that causes significant economic losses to chicken and turkey producers worldwide. The currently available live attenuated and inactivated vaccines provide limited protection. The objective of this study was to identify potential subunit vaccine candidates using immunoproteomics and reverse vaccinology analyses and to evaluate their preliminary protection. Twenty-four candidate antigens were identified, and five of them, namely RS01790 (a putative s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…First of all, these may be explained by the fact that mycoplasmas cytadherence is a complex, multifactorial process involving numerous membrane proteins and cytoskeletal elements ( 11 ). In addition to the antigens used in the present study, other proteins have also been proven to contribute to the adhesion process of MS ( 12 ). Secondly, the limited protective effect on the colonization of MS in the trachea may be attributed to the lack of specific antibodies in the trachea, which is consistent with earlier findings in MG .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…First of all, these may be explained by the fact that mycoplasmas cytadherence is a complex, multifactorial process involving numerous membrane proteins and cytoskeletal elements ( 11 ). In addition to the antigens used in the present study, other proteins have also been proven to contribute to the adhesion process of MS ( 12 ). Secondly, the limited protective effect on the colonization of MS in the trachea may be attributed to the lack of specific antibodies in the trachea, which is consistent with earlier findings in MG .…”
Section: Discussionmentioning
confidence: 99%
“…The adhesion of mycoplasma to host cells is a prerequisite for colonization and infection ( 11 ). Recently, subunit vaccines contain proteins that are involved in MS adherence showed effectively protect against MS infection ( 12 , 13 ). In infection caused by Mycoplasma gallisepticum ( MG ), another important avian mycoplasma, vaccines containing adherence proteins imparted protective immunity in chickens ( 14 , 15 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Membrane proteins are key Mycoplasma proteins and are integral to various microbial activities. Recent studies have demonstrated that multiepitope subunit vaccines constructed with immunogenic membrane proteins signi cantly enhance protection against M. synoviae [20,21]. Therefore, the identi cation and screening of M. synoviae immunogenic proteins is bene cial for vaccine development and infection prevention.…”
Section: Introductionmentioning
confidence: 99%
“…Reverse vaccinology has been extensively used for the screening of vaccine candidates for various pathogens, such as serogroup B Neisseria meningitidis ( menB ) [ 25 ], Acinetobacter baumannii [ 26 ], Brucella spp. [ 27 ], Shigella dysenteriae [ 28 ], and Mycoplasma synoviae [ 29 ]. With this approach, menB vaccines have been successfully developed [ 25 ].…”
Section: Introductionmentioning
confidence: 99%